Influence of uterine inflammation on the estrous cycle in rats - Kaneko, K. (Azabu Univ., Sagamihara, Kanagawa (Japan)); Aoki, H; Furuichi, T; Hatori, S; Tanimoto, H; Kawakami, S (Journal of Reproduction and Development, 2004)
To investigate how uterine inflammation affects ovarian activity in rats, endometritis was induced and changes in the length of estrous cycle and serum concentrations of estradiol-17beta (E2) and progesterone (P4) were examined. A suspension of Staphylococcus aureus (bacterial solution) or iodine solution was infused into the uterine lumen at various estrous phases. When the bacterial solution was infused at estrus, metestrus, or the first day of diestrus, the following diestrus continued for 5 to 12 days. In the case of the iodine solution, regardless of the estrous phase of the infusion, the following diestrus continued for approximately 6 days. E2 concentration after infusion of each solution did not fluctuate largely and remained at a low concentration (around 5 pg/ml). P4 concentration was high (35-45 ng/ml) on the day following infusion, but decreased rapidly to base line values within a few days and remained thereafter at a low level (around 5 ng/ml). It is assumed that the endometritis caused by biological or chemical stimulation raises the concentration of P4 to depress gonadotrophic hormone secretion, and hence this high P4 concentration might inhibit the growth of ovarian follicles.